KAMPANYE #BERKAINGEMBIRA DALAM MEMBANGUN KESADARAN GENERASI Z AKAN BUDAYA BERKAIN (E-Jurnal Medium, 2022)
The purpose of this research is to find out how #BerkainGembira campaign builds awareness of Generation Z on berkain culture. #BerkainGembira campaign is a digital campaign that aims to transfer knowledge about berkain culture. This study uses qualitative method with descriptive approach. Data was collected through online interviews, online observations, and documentation studies. AIDDA concept is used to analyze the message conveyed by the #BerkainGembira campaign. Two-Step Flow communication model is used to analyze the use of public figures and influencers as communicators. The results in this study show #BerkainGembira campaign can build awareness of Generation Z on berkain culture. #BerkainGembira campaign is carried out through social media, namely Instagram, TikTok, Youtube, and Discord through creative content sharing and hashtag that became a trend among Generation Z and forming a community network. The involvement of public figures and influencers in the #BerkainGembira campaign also attracted Generation Z to this campaign. Keywords: #BerkainGembira Campaign, Awareness, Generation Z, Berkain Culture